An Evaluation of Community Satisfaction on Engaging in Disciplinary Hours for Minors in Selected Barangays in Dasmarinas City, Cavite - Bangit, Jose Luis I.; Dela Pena, Mary Jane V.; Mojica, Edralyn; Sotto, John Robert G.; Tagalog, Eden Mae D.; Villanueva, Arthur; Villa, Elizabeth; Mobo, Froilan D.; Golla, Nathaniel S. (Future Science / FSH-PH Publications, 2025)
This study aims to evaluate community satisfaction with the im-plementation of disciplinary hours for minors in selected baran-gays of Dasmariñas City, Cavite. It focuses on addressing issues involving minors in conflict with the law. The participants include police personnel, barangay officials, and parents from Barangays Sta. Fe, San Nicolas I, and San Francisco 2. A quantitative-descriptive design was employed, using surveys to gather data on the participants' demographic profiles and factors contributing to minors' involvement in criminal activities. Findings revealed that while curfew measures are seen as effective and well-implemented, their associated costs are perceived as insignificant. To address habitual offending, the researchers recommend an awareness or intervention program involving the Department of Social Welfare and Development (DSWD). This initiative would provide counseling and promote social responsibility among mi-nors, fostering active citizenship and unity to eliminate minor crimes in the area.